Sankofa: Traditions of Mentoring Among Black Women Educators - (:unkn) unknown (My University, 2014)
The importance of the standpoint of Black women educators is rarely understood and even more infrequently recognized as a position of exceptional knowledge in regard to the field of education. Research highlights maternal relationships grounded in traditional practices of community uplift and connectedness as a common factor in the effectiveness of Black women educators. This project frames Black women educators within Black women's culture of Sisterhood and Motherhood as defined by Patricia Hill Collins (2009). This study explored the influence of sisterhood and motherhood in the experiences of Black women educators and the impact of those experiences on their work as educators. The analysis derived from a series of four semi-structured interviews and informal follow-up conversations with three of my close sister friends who are educators in a Midwest Public school system. Three narrative portraits of Black women educators were created based on a 6-month portraiture study involving the collection of observable data, semi-structured and informal interviews and discourse analysis to capture the perspective of Black women educators in the field of education. Through an examination of this portrait study and other studies on Black women's culture and pedagogical engagement, this project provides examples of Black women educators who embody the essence of Sankofa in the form of mentoring. Findings indicated that mentoring among Black women educators builds on a tradition of sisterhood and motherhood in the Black community. These findings provide three culturally relevant components apparent in the mentoring experiences of these participants: self-actualization, socio-political awareness and mothering of the mind.
Keywords: Black Feminism; Black Women Educators; Othermothering; Sisterhood; Teacher Mentorship